ASUMSI PUBLIK TERHADAP PASAL 51 KITAB UNDANG-UNDANG HUKUM PIDANA SEBAGAI DASAR IMUNITAS PEJABAT NEGARA - Orien Effendi (Fakultas Hukum, Universitas Samudra, 2020)
AbstractMany people consider that the existence of Article 51 paragraph (1) and (2) in the Criminal Code is a basis for absolute immunity or immunity for officials. No exception for ordinary people who ultimately know the contents of the article who then assume that the law we profess is very damaging to a sense of justice. The existence of this article has also attracted the attention of academics, as evidenced by the number of studies published in publications that we can find in online media. It is this community's assumption that will lead to a setback of the law itself because of the loss of public trust in the existing legal system. Position orders without authority, do not cause criminal abolition, except if the governed, in good faith thinks that the order is given with authority and its implementation is included in the work environment, that is about the sound of paragraph (2) of article 51 of the Criminal Code. The problem that often occurs is that many articles in legislation do not explain in detail the true meaning. If we may examine paragraph (2) in that article, it means that an official's actions can be justified even though there is no prior order, either from the law or an order of an authorized position with only the basis of good faith from the act. The intent of good faith can invite diverse interpretations, then questions arise; what are the criteria of good faith, whichever boundary of good faith is intended, and so on.Keywords: Article 51, Criminal Code, Academics, Justice.